2014
DOI: 10.1002/app.41390
|View full text |Cite
|
Sign up to set email alerts
|

PEG 400/Paraffin oil non‐aqueous emulsions stabilized by PBut‐BlockP2VP block copolymers

Abstract: For the preparation of PEG 400 in paraffin oil non-aqueous biocompatible emulsions, the stabilization efficiency was compared for two well-defined poly(butadiene)-block-poly(2-vinylpyridine) (PBut-block-P2VP) block copolymers, with similar molecular weights but different compositions. The PBut 128 -block-P2VP 50 and PBut 189 -block-P2VP 37 samples, designated as copolymer A and B, respectively, are self-organized in paraffin oil as micelles with a P2VP core and a PBut corona. The PEG 400/paraffin oil emulsion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The bulk 3D-rheology in which an emulsion prepared with the two fluids and the particles is subjected to periodic shear or squeeze deformations obtain the 3D viscosity and elasticity of the emulsion as a function of the shear or squeeze rate and time. This bulk characterization provides important information concerning the flow behaviour and the stability of the emulsions, useful for practical applications [20]. Moreover, this can be performed at the same time as the real structure of the emulsion is obtained by confocal microscopy [25].…”
Section: Characterization Of Interfacial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The bulk 3D-rheology in which an emulsion prepared with the two fluids and the particles is subjected to periodic shear or squeeze deformations obtain the 3D viscosity and elasticity of the emulsion as a function of the shear or squeeze rate and time. This bulk characterization provides important information concerning the flow behaviour and the stability of the emulsions, useful for practical applications [20]. Moreover, this can be performed at the same time as the real structure of the emulsion is obtained by confocal microscopy [25].…”
Section: Characterization Of Interfacial Activitymentioning
confidence: 99%
“…When the water phase is replaced by a polar solvent like propylene glycol [11], glycerol [12,13], formamide [14,15,13,16,17] or methanol [18], the solvent-oil interface is expected to retain the essential physics as that with the water phase [9]. On the other hand, the cases of liquid polymer-oil [19,20,21,22,23] and immiscible liquid polymer blends [24] [ 25,26,27,28,29,30,31,32,33,34] [35,36,37,38,39,40,41,42] [43,44] are quite different and reported more frequently in the literature due to their important industrial applications. Nevertheless, we want to stress also the less studied case of true oil-oil interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Our research group studied the micellization of P2VP- b -PEO diblock copolymers in several biocompatible solvents, such as PEG400 (δ = 21.3 MPa 1/2 ), paraffin oil (δ = 15.3 MPa 1/2 ), and Miglyol 812 (δ = 17.3 MPa 1/2 ) [ 73 , 74 , 75 ]. Spherical micelles, having a P2VP core and a R h in the range of 23 to 25 nm were obtained by the self-assembly of P2VP 37 - b -PB 189 copolymer sample in paraffin oil and Miglyol 812, which is a glycerine ester.…”
Section: Ab and Aba Linear Block Copolymers In Organic Solventsmentioning
confidence: 99%
“…In this type of emulsion, usually designated as oil-in-oil (O/O) emulsion, the monomer droplets are dispersed in a non-miscible oil and the stabilization can be achieved by using tailor-made copolymers. It has been shown that copolymers can provide longer stability for O/O emulsions with respect to the conventional surfactants because they have a much slower desorption kinetics at the interface of the droplets [21][22][23][24]. Moreover, it is well known that PNVP, which is FDA approved, is a hydrophilic polymer and has a good efficiency to control the release rate of poorly water-soluble drugs [25].…”
Section: Introductionmentioning
confidence: 99%